Firm exit and liquidity: Evidence from the Great Recession - Fernando Leibovici; David Wiczer (Federal Reserve Bank of Atlanta, 2024)
This paper studies the role of credit constraints in accounting for the dynamics of firm exit during the Great Recession. We present novel firm-level evidence on the role of credit constraints on exit behavior during the Great Recession. Firms in financial distress, with tighter access to credit, are more likely to default than firms with more access to credit. This difference widened substantially in the Great Recession while, in contrast, default rates did not vary much by size, age, or productivity. We identify conditions under which standard models of firms subject to financial frictions can be consistent with these facts.
Keywords: E32; G01; 330; firm exit; Great Recession; credit constraints; financial distress